Celebration issues of the invited papers for Professor Ihor Yukhnovskii (Condensed Matter Physics, 2000)
On September 1, 2000 Academician, Professor Ihor Yukhnovskii, a prominent Ukrainian scientist and a founder of the Lviv school of statistical physics, will celebrate his 75th birthday.